Operation of a virtual keyboard based on EMG Signals - Tiarma Simanihuruk; Jimmy Jimmy; Jati Putra (Politeknik Ganesha Medan, 2024)
We demonstrate the operation of a virtual keyboard utilizing electromyography signals derived from finger movements. Initially, we identify human arm surfaces corresponding to specific finger motions, where EMG sensors are subsequently placed. The raw EMG signals obtained from our setup undergo filtration using a custom-made electric circuit. A LabVIEW program is employed to measure and manage these EMG signals. Following the conversion of analog signals to digital format, the data is inputted to an Arduino board, which then displays the corresponding letters from the virtual keyboard onto a computer monitor. The success of this demonstration is contingent upon a training session adhering to the established protocol.